ASSESSMENT Of DIVERSITY OF WADING BIRDS AND SHOREBIRDS ON ADEN LAGOONS, YEMEN: Abeer Yousuf Fadle Qardash1*and Jaafar Omar Baomar2 - Qardash, Abeer Yousuf (Journal of King Abdulaziz University: Marine Sciences, 2025)
Almost all habitats on the planet are home to birds, from the lowest deserts to the highest mountains. Birds have proved to be excellent indicators of biodiversity or productivity as they are easily observed and are relatively well known compared to other animals. This study aims to assess wading birds and shorebirds diversity in the Aden lagoons from October 2021 to December 2022. fifty four species belong to seven families of shorebirds and five families of wading birds were recorded in the study area. A highest relative abundance 14.78 % was recorded in June 2022, while the lowest was 3.03 % recorded in April 2022. The highest values of Simpson diversity index and Shannon-Weiner index were 0.95 and 3.25, respectively. Species richness index reached 5.432, while an evenness index was 0.862. Dominance index recorded a high value in November 2021, July 2022, August 2022, September 2022and November 2022. The assemblage of wading birds and shorebirds at Aden lagoons was moderate, whereas showed disturbed and semi-balanced assemblage in terms of the richness and evenness respectively.